2001
DOI: 10.7326/0003-4819-134-3-200102060-00009
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Enoxaparin Once or Twice Daily Compared with Intravenous Unfractionated Heparin for Treatment of Venous Thromboembolic Disease

Abstract: Subcutaneous enoxaparin once or twice daily is as effective and safe as dose-adjusted, continuously infused unfractionated heparin in the prevention of recurrent symptomatic venous thromboembolic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
148
2
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(162 citation statements)
references
References 36 publications
5
148
2
7
Order By: Relevance
“…In this cohort of postarthroplasty patients, the incidence of major bleeding complications (10%) was substantially higher than the rates reported for nonsurgical patients, which are 0% to 5% [5,20,22,35]. This difference highlights the unique risks inherent to anticoagulation treatment in patients who have undergone procedures, which include substantial soft tissue dissection and osteotomies.…”
Section: Discussionmentioning
confidence: 63%
“…In this cohort of postarthroplasty patients, the incidence of major bleeding complications (10%) was substantially higher than the rates reported for nonsurgical patients, which are 0% to 5% [5,20,22,35]. This difference highlights the unique risks inherent to anticoagulation treatment in patients who have undergone procedures, which include substantial soft tissue dissection and osteotomies.…”
Section: Discussionmentioning
confidence: 63%
“…Two articles did report the cancer subgroups data. 12,13 Three other articles [14][15][16] had follow-up publications reporting the cancer subgroup data. [17][18][19][20] We contacted the authors of the remaining 19 articles to request cancer subgroup data: One author provided us with the data 21 ; another author indicated that the data were not available anymore 22 ; we used the cancer subgroup data for 7 articles, 23-29 because they were reported in 2 published systematic reviews 5,8 ; and we were not able to obtain any outcome data for the remaining studies.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Patients with cancer, as noted earlier, constituted subgroups in all studies that were included. [12][13][14][15][16]21,[23][24][25][26][27][28][29] The 13 studies recruited a total of 1016 patients with cancer and 4797 patients without cancer. None of the studies specified the type(s) of cancer of participants.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Thus, the increased risks of major bleeding during anticoagulation in fragile patients could be explained, at least in part, by these other drugs that might have potentiated the effect of the anticoagulant therapy. The similar risk for bleeding than for VTE recurrences in VTE patients weighing ≤50 kg has not been consistently reported 26, 27, 28. These findings suggest the potential benefit of tailored therapy for VTE according to clinical characteristics of the patients and warrant external validation.…”
Section: Discussionmentioning
confidence: 85%